Indonesian Poetry Song Composition in Musicology Perspective - Kartini Ruth Maduma Manalu; G. R. Lono Lastoro Simatupang; Nyak Ina Raseuki (Jurnal Kajian Seni, 2022)
This research is an attempt by the author to answer various debates that exist to this day. This debate is often a stumbling block for musicians and also in the field of formal and non-formal education. They are in a confusing position because of the various terms that exist and the identification of the concept of Indonesian vocal music composition which is less comprehensive. Therefore, there is a personal selfishness that tends to reduce the true meaning of the work itself. The author uses a musicological perspective as an entry point to provide a new discourse regarding the composition of Indonesian vocal music. This musicological approach is a process of study, investigation and reflection while still paying attention to the relationship between context and compositional work. The author is also aware of the limitations of the space and time of the research, so that this research is not possible to fully cover all vocal music works composed by Indonesian composers. However, the author believes that the research approach carried out can be used to discuss other vocal music works.